Walking with the Dead - Bowler, Tim (Hodder Children's Books, 2006)
Stevie is having an unhappy time with his father and his father's girlfriend. In a rage he storms off and in a quiet courtyard he sees a strange, old man. Stevie takes the broken bell the man leaves behind and that night he wakes to find ghostly figures in his room. Stevie finds himself drawn into their medieval world. Outcasts, excluded from the town, they tell Stevie that the old man, their grandfather, is bent on risking everything to enter the town one last time. Stevie joins in following the old man to try to protect him from the pitiless mob of townsfolk. In a dramatic climax Stevie faces the fury of the crowd and in doing so begins to understand what it is to be an object of hate.
Keywords: Juvenile literature-Ghosts-Horror-The Dead-Fiction